Proximal medial gastrocnemius release: Muscle strength evaluation. Issue 7 (October 2020) - Busquets, Rosa; Sanchez-Raya, Judith; Sallent, Andrea; Maled, Iñaki; Duarri, Gemma
Highlights: Proximal medial gastrocnemius release not only avoids strength loss but gains strength, as opposed to Achilles lengthening. Proximal medial gastrocnemius release improves function and mobility without decreasing strength. The strength in the asymptomatic limb is higher than the pathological limb both before and after surgery. Abstract: Background: Contracture of the gastrocnemius has been associated with different foot and ankle pathologies. The present study's aim is to evaluate the effect of the proximal medial gastrocnemius release (PMGR) in triceps surae strength. Methods: Prospective study with 14 patients (12 women; mean age 52 years). Inclusion criteria were patients undergoing PMGR due to forefoot and/or hindfoot injury with medial gastrocnemius contracture that has not improved with physical therapy. Isometric and isokinetic force evaluation tests with an isokinetic dynamometer (Con-Trex) were performed preoperatively, at 6 and 12 months postoperative, of both limbs. Results: After isokinetic assessment, the statistically significant difference in the preoperative isometric strength of the triceps between the two ankles was confirmed, being stronger the asymptomatic limb. An improvement in the triceps strength in isokinetics was observed at 60°/s at 6 months after surgery (p = 0.008), that was maintained after one year (p = 0.05). No differences were observed at 120°/sec speed. Conclusion: Patients with gastrocnemius contracture present a decrease in isometric force with respect to the asymptomatic limb preoperatively. There is an improvement in isokinetic strength after 6 months postoperatively.